2017
DOI: 10.3892/or.2017.5425
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a-5p, an inducer of Wnt-signaling, facilitates cell proliferation in acute lymphoblastic leukemia

Abstract: Uncontrolled Wnt signaling causes leukemia. Inactivation of Wnt antagonists could play an important role in leukemia progression by activating the Wnt/β-catenin pathway. Wnt inhibitory factor-1 (WIF1) is one of the important Wnt antagonists. Few miRNAs have been reported to directly target this gene in hematopoiesis. Here, we observed that miR-181a-5p expression was markedly overexpressed in several leukemia cell lines and acute lymphoblastic leukemia (ALL) samples compared with that noted in normal peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…miR‐342‐3p has not previously been associated with OS in miRNA profiling studies. miR‐181a‐5p has been shown to downregulate a Wnt antagonist, thereby activating the Wnt signaling, which is, as described above, important for the differentiation of osteoprecursor cells into OB cells (Lyu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…miR‐342‐3p has not previously been associated with OS in miRNA profiling studies. miR‐181a‐5p has been shown to downregulate a Wnt antagonist, thereby activating the Wnt signaling, which is, as described above, important for the differentiation of osteoprecursor cells into OB cells (Lyu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Xin et al 27 have indicated that Dishevelled-Axin domain-containing 1 could promote acute myeloid leukemia cells growth via regulating Wnt/βcatenin pathway. Lyu et al 28 suggested that miR-181a-5p could facilitate cell proliferation in ALL by activating Wnt/ β-catenin pathway. In addition, cyclin D1 is necessary for the progression of the cell cycle, and its overexpression has Figure 7 GAS2 activated Wnt/β-catenin pathway in Jurkat and CCRF-CEM cells.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of WIF1 could activate Wnt/β‐catenin signaling to promote cell proliferation (Lyu et al . ). We thus suggest that the nonconservative substitution probably alters WIF1 interactivity with protein partners and consequently affects gene function.…”
Section: Mutations Identified In Wif1 and Hmga2 Genesmentioning
confidence: 97%